Radiographic investigation on degree of canal curvature in human maxillary anterior teeth in Babol, Iran - Abesi, Farida; Ehsani, Maryam (Iranian Endodontic Journal, 2011)
Introduction: Complete knowledge of root canal curvature is a critical factor in successful dental treatment .The aim of this study was to investigate the direction, radius and degree of curvature of maxillary anterior teeth and the relation between radius and degree of curvature in Babol city. Methods &materials: This study was performed on 242 anterior teeth radiographs were taken by periapical parallel technique and processed by automatic processing. The degree of canal curvature was measured only at mesiodistal direction with Schneider method and classified according to Seidberg method .Statistical analysis was performed by Kruskal Wallis. Results: Out of 242 examined teeth, 153(%62) had curvature that %35.3of them had mesially curve and %64.7 had distally curve. The degree of canal curvature was observed as following: %39.3 with small curvature, %44.6 with intermediate and %16.1 with sever curvature. Also the degree of curvature of central teeth was: 7.2°±9.03°, lateral: 12°±11°and canine: 15°±12°.There was significant correlation between type of tooth and degree of curvature (p=0.000). But there wasn't significant correlation between type of tooth and radius curvature. (p=o.365) Conclusion: In present study, %62 of maxillary anterior teeth had curve and the most degree of curvature was related to the canines. Also it was seen inverted correlation between radius and degree of root curvature but it was insignificant. Keywords: Maxillary anterior teeth, Radius of curvature, Root curvature.